2014
DOI: 10.1016/j.jphotobiol.2013.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Sak1 kinase interacts with Pso2 nuclease in response to DNA damage induced by interstrand crosslink-inducing agents in Saccharomyces cerevisiae

Abstract: By isolating putative binding partners through the two-hybrid system (THS) we further extended the characterization of the specific interstrand cross-link (ICL) repair gene PSO2 of Saccharomyces cerevisiae. Nine fusion protein products were isolated for Pso2p using THS, among them the Sak1 kinase, which interacted with the C-terminal β-CASP domain of Pso2p. Comparison of mutagen-sensitivity phenotypes of pso2Δ, sak1Δ and pso2Δsak1Δ disruptants revealed that SAK1 is necessary for complete WT-like repair. The ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Therefore, if formation of PSO2/SNM1‐containing DNA repair complexes at the site of ICL damage does involve PCNA ubiquitylation, then the molecular mechanisms underlying TbSNM1 recruitment to such lesions occurs through an as yet uncharacterised UIM or via interactions involving a conserved adapter protein. Recently, it has been shown that the β‐CASP domain of Pso2p can be phosphorylated leading to the suggestion that this event may play a role in modulating the enzyme's exo‐ or endo‐nucleolytic activity (Munari et al ., ). Whether TbSNM1 undergoes a similar post‐translational modification, and how this effects its nuclease activity has yet to be established.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, if formation of PSO2/SNM1‐containing DNA repair complexes at the site of ICL damage does involve PCNA ubiquitylation, then the molecular mechanisms underlying TbSNM1 recruitment to such lesions occurs through an as yet uncharacterised UIM or via interactions involving a conserved adapter protein. Recently, it has been shown that the β‐CASP domain of Pso2p can be phosphorylated leading to the suggestion that this event may play a role in modulating the enzyme's exo‐ or endo‐nucleolytic activity (Munari et al ., ). Whether TbSNM1 undergoes a similar post‐translational modification, and how this effects its nuclease activity has yet to be established.…”
Section: Discussionmentioning
confidence: 97%
“…Alternatively, or in addition, yet unidentified post-translational modification of Pso2 may regulate its intracellular distribution. Concordant with this idea, phosphorylation of Pso2 has been shown to modulate its exo- or endo-nucleolytic activity (Munari et al . 2014).…”
Section: Discussionmentioning
confidence: 77%
“…This situation resembles that noted in other organisms although there are some key differences. In S. cerevisiae , PSO2 (the yeast SNM1 homologue) displays a non-epistatic interaction with EXO1 and all tested DSB repair protein, including MRE11 [45, 72, 74, 75]. It also associates with several NER factors such as RAD1 (XPF), RAD3 (XPD), RAD4 (XPC) and RAD14 (XPA) [22, 72] although whether it interacts with RAD26 (the yeast CSB homologue) remains unclear [22].…”
Section: Discussionmentioning
confidence: 99%